Penerapan Model Pembelajaran Creative Problem Solving untuk Meningkatkan Hasil Belajar dan Kreativitas Siswa Kelas IV SDN 02 Josenan - Kasih Septin Pangestu; Heny Kusuma Widyaningrum; Siti Khuzaimah (Atmosfer: Jurnal Pendidikan, Bahasa, Sastra, Seni, Budaya, dan Sosial Humaniora, 2024)
This research is motivated by the low level of student activity and learning outcomes in science and science learning. This research aims to increase student activity and learning outcomes in class IV SDN 02 Josenan by applying the creative problem solving (CPS) learning model. The research method used by researchers is classroom action research in collaboration with class IV teachers at SDN 02 Josenan, with a total of 29 class IV students. This research took place in 2 cycles. The techniques used in data collection are observation, tests, interviews, documentation. The research results show that implementing the Creative Problem Solving (CPS) learning model can increase student activity and learning outcomes in science and technology learning in class IV SDN 02 Josenan. Learning outcome data proves this. From cycle I to cycle II, student activity increased in cycle I by 67.42% to 83.14% in cycle II. The average score for student learning outcomes is 74.5, with the lowest score being 52 and the highest score being 97, while the percentage of completion of classical learning outcomes is 69.96%. In cycle II, the average score for student learning outcomes was 84.5, with the lowest score being 69, and the highest score being 100, and the percentage of completeness of classical learning outcomes was 89.65%.